Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. Issue 11 (18th June 2014) - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini
Abstract : Objective: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. Design: Cross-sectional study. Setting: Tertiary care centre in north India. Patients: Children, aged 2–18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. Results: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. Conclusions: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.